ANALISA PENGARUH VARIASI TEGANGAN LISTRIK DAN JARAK ANODA DENGAN KATODA PADA PROSES ANODISASI TERHADAP TINGKAT KILAP MATERIAL KOMPOSIT AL – ABU DASAR BATUBARA - Santoso, Edi; Rohman, Fatehur (MEKANIKA: Jurnal Teknik Mesin, 2015)
Composites have been developed in the world of manufacturing especially Metal Matrix Composites ( MMCs ). It is light resistant to corrosion, and mechanical properties has been successfully repaired in variousstudies, make this material superior in terms of durability. But the appearance need to be improved to obtain a highdecorative value through anodizing process. Coloration process using this anodizing method has been used forcoloring aluminum metal. Anodizing process carried out by the independent variable electrical voltage between 8,10, and 12 Volt and anode cathode distance 0.10, 0.15, and 0.20 m with 10 minutes of processing time. Colorationresults are tested using test equipment gloss sheen Micro-Tri-Gloss with reflection angle of 85. The results showedthat the variation of the electric voltage supplied to the anodizing process proved to be able to give much influenceon the vulnerable 8 , 10 , and 12 Volt. Material reflectance values tend to decrease. This happens because thehigher the voltage , the greater the material pore. The same is shown on the chart the influence of sulfuric acidconcentration and the voltage of the pore diameter. In the graph shows an increase continuously - as you constantlygiven electrical voltage. Anode cathode distance variation on the anodizing process also proved sufficient to providea significant influence on susceptible 0.10 , 0.15 , and 0.20 m. Material reflectance value tends to increase with theaddition of anode cathode spacing. Such things happen because of the obstacles posed increasingly stable , theformation of smaller pore structure and equitable causes deposition of dye attached to the surface of the object isflat and the color quality is increasing. The highest reflectance values obtained at a voltage of 8 volts of electricitywith the anode cathode spacing 0.15 m. While the lowest reflectance values obtained at a voltage of 10 volts ofelectricity with the anode cathode spacing 0.10 m.Keywords : anodizing , voltage, anode cathode spacing , reflectance